An Analysis of Relationship between the Microfracture Features and Mineral Morphology of Granite - Meiben Gao; Tianbin Li; Junxun Zhu; Hongyu Yin; Yongyi Yang (Advances in Civil Engineering)
Using the techniques of X-ray diffraction, polarizing microscopy, uniaxial compression, and scanning electron microscopy (SEM), the relationships between the microfracture features and mineral morphology of granite were studied. The results showed that feldspar, quartz, and biotite are the main components of the granite samples in this study. Biotite has a self-shaped flake structure with perfect cleavage. K-feldspar has a lattice double crystal structure with two groups of cleavage. Plagioclase has a semi-self-shaped plate structure with two groups of cleavage. Quartz is prismatic or granular and exhibits noncleavage. The microfracture features of biotite are flaky with exfoliation, and flake cleavage fracture is mainly determined by its peculiar flaky cleavage. Feldspar (K-feldspar and plagioclase) is plate, layered, or two groups of cleavage and is also mainly determined by its peculiar two groups of cleavage. The microfracture features of quartz are highly irregular, with many randomly distributed intergranular and transgranular cracks, small particles or granule bulges, similar to quartz crystal, and this is due to the noncleavage feature of quartz itself. It is demonstrated that microfractures are preferentially ruptured along cleavage planes for these granite minerals under the action of external forces.